Low-dielectric glass fiber composition, low-dielectric glass fiber and preparation method of low-dielectric glass fiber
By using components such as SiO2 and B2O3 in glass fibers, combining specific alkaline earth metal oxides and other oxides, and jointly controlling the proportion of components, the problem of insufficient dielectric performance and process performance of existing glass fibers is solved, and the effects of low dielectric constant and low dielectric loss are achieved.
Patent Information
- Application Number
- CN202411955180.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-18
AI Technical Summary
The existing glass fiber has poor dielectric performance and poor process performance, making it difficult to meet the needs of high-frequency and high-speed lines.
SiO2 and B2O3 are used as main components, combined with specific types of alkaline earth metal oxides, Al2O3, ZrO2, TiO2, LiO2 and F2, and low dielectric glass fibers are prepared by collaboratively controlling the proportion of each component.
It significantly reduces the dielectric constant and dielectric loss of glass fibers, while improving process performance, ensuring the stability and excellent dielectric properties of glass fibers.
Smart Images

Figure BDA0005215617960000101 
Figure BDA0005215617960000111 
Figure BDA0005215617960000121
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of glass fiber preparation, and in particular to a low-dielectric glass fiber composition, a low-dielectric glass fiber and a preparation method thereof. Background Art
[0002] With the rapid development of the electronics field, the new generation of high-speed routers, switches, communication base stations and high-end servers require high-frequency and high-speed lines to meet the growing demand for data transmission and processing speeds. The performance of these devices depends largely on the performance of high-frequency communication copper clad laminates (PCBs). In order to reduce energy consumption during signal transmission and improve the quality of signal reception, PCB boards need to have the lowest possible dielectric constant and dielectric loss. Low dielectric constants can reduce signal delays and increase signal transmission speeds; low dielectric loss helps reduce signal attenuation during transmission, ensure signal integrity and clarity, and reduce energy loss.
[0003] Glass fiber is often used as a reinforcing material for PCB boards due to its excellent mechanical properties and electrical insulation properties. In addition to low dielectric constant and low dielectric loss, the substrate of PCB boards also needs to have other properties, such as thinness, good processability, low thermal expansion coefficient, etc., to adapt to precision manufacturing processes and ensure the reliability of equipment. Therefore, low dielectric glass fiber is an indispensable engineering material in high-end communications, aerospace and other fields.
[0004] At present, E glass fiber and D glass fiber are widely used at home and abroad. The composition of E glass fiber is: SiO2: 52% ~ 56%, Al2O3: 12% ~ 16%, B2O3: 5% ~ 10%, CaO: 16% ~ 25%, MgO: 0% ~ 5.0%, Na2O and K2O: 3% ~ 5%. The advantages of E glass are good processability, strong water resistance and low price, but the dielectric constant is high (about 6.7) and the dielectric loss is large (greater than 10 -3 ), not suitable for high-density and high-speed information processing. D glass fiber composition: SiO2: 72% ~ 76%, Al2O3: 0% ~ 5%, B2O3: 20% ~ 25%, Na2O and K2O: 3% ~ 5%. The advantages of D glass are low dielectric constant (about 4.1) and low dielectric loss (about 8×10 -4 ), but due to the high SiO2 content, the drilling performance is poor, which is not conducive to subsequent processing; and the glass has a high softening point and poor melting properties, which easily produces veins and bubbles, making the wire drawing operation difficult, resulting in many broken wires, and poor productivity and operability.
[0005] Based on this, there is an urgent need to provide a low dielectric glass fiber composition, a low dielectric glass fiber and a preparation method thereof. Summary of the invention
[0006] The embodiments of the present invention provide a low-dielectric glass fiber composition, a low-dielectric glass fiber and a preparation method thereof, which can solve the problems of poor dielectric properties and poor process performance of traditional glass fibers.
[0007] In a first aspect, the present invention provides a low dielectric glass fiber composition, which comprises the following components, in molar percentage: SiO2: 54-60%, B2O3: 21-32%, Al2O3: 1.0-9.5%, alkaline earth metal oxide: 3-16%, ZrO2: 0.01-4.0%, TiO2: 0.1-4.0%, LiO2: 0.01-2.0%, F 2 : 0.5~5.0%; wherein the alkaline earth metal oxide includes CaO and MgO, in molar percentage, CaO is 0.01~4.0%, and MgO is 0.5~8.0%.
[0008] Preferably, the sum of the molar percentages of SiO2 and B2O3 is 78 to 85%.
[0009] Preferably, the alkaline earth metal oxide further comprises BaO and SrO; wherein, in molar percentage, BaO is 0.01-2.0%, and SrO is 0.01-2.0%.
[0010] Preferably, the ratio of B2O3 to the alkaline earth metal oxide is 2.5 to 7 in mole percentage.
[0011] Preferably, the low dielectric glass fiber composition further comprises: ZnO, Y2O3 and P2O5; wherein, in molar percentage, ZnO is 0.01-5.0%, Y2O3 is 0.01-0.6%, and P2O5 is 0.01-2.0%.
[0012] Preferably, the sum of the molar percentages of ZrO2 and Y2O3 is 0.2-2%.
[0013] Preferably, F 2 The sum of the molar percentages of P2O5 and P2O5 is 0.6-7%.
[0014] Preferably, the low dielectric glass fiber composition comprises the following components, in molar percentage: SiO2: 55.5-58%, B2O3: 21.5-31.5%, Al2O3: 1.0-5.0%, alkaline earth metal oxide: 3-10%, ZrO2: 0.01-1.0%, TiO2: 0.5-3.5%, LiO2: 0.01-2.0%, F 2: 0.5-5.0%, ZnO: 0.05-4.0%, Y2O3: 0.05-0.5%, P2O5: 0.05-2.0%; wherein the alkaline earth metal oxides include CaO, MgO, BaO and SrO, in molar percentage, CaO is 0.3-4.0%, MgO is 0.9-7.5%, BaO is 0.02-1.5%, SrO is 0.02-1.5%.
[0015] In a second aspect, the present invention provides a method for preparing low dielectric glass fiber from the low dielectric glass fiber composition according to any one of the first aspects, the method comprising the following steps:
[0016] (1) stirring and mixing each component according to mole percentage to obtain a low dielectric glass fiber composition;
[0017] (2) melting the low dielectric glass fiber composition to obtain homogeneous glass;
[0018] (3) Drawing the homogeneous glass to obtain the low dielectric glass fiber.
[0019] In a third aspect, the present invention provides an application of the low dielectric glass fiber described in the second aspect in a high-frequency circuit board.
[0020] Compared with the prior art, the present invention has at least the following beneficial effects:
[0021] In the present invention, SiO2 and B2O3 are used as the main components of the glass, and SiO2 can serve as a network former of the glass structure. On the one hand, part of B2O3 can form a [BO4] tetrahedral structure and enter the glass silicon oxygen network structure, thereby playing a role in network reinforcement. On the other hand, B2O3 can effectively inhibit ion polarization and thus reduce the dielectric constant and dielectric loss of the glass fiber. By adding specific types of alkaline earth metal oxides and supplemented with a certain amount of Al2O3, ZrO2, TiO2, LiO2 and F2, the dielectric constant and dielectric loss of the glass fiber can be further reduced. At the same time, through the coordinated control of each component, it is beneficial to enhance the process performance of the glass and ensure the stability of glass fiber drawing. DETAILED DESCRIPTION
[0022] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0023] An embodiment of the present invention provides a low dielectric glass fiber composition, which comprises the following components in molar percentage: SiO2: 54-60% (for example, 54%, 54.5%, 55%, 55.5%, 56%, 56.5%, 57%, 57.5%, 58%, 58.5%, 59%, 59.5%, or 60%), B2O3: 21-32% (for example, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31% or 32%), Al2O3: 1.0-9.5% (for example, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0%, 7.5%, 8.0%, 8.5%) , 9.0% or 9.5%), alkaline earth metal oxides: 3-16% (for example, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15% or 16%), ZrO2: 0.01-4.0% (for example, 0.01%, 0.1%, 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5% or 4 .0%), TiO2: 0.1-4.0% (for example, 0.1%, 0.1%, 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5% or 4.0%), LiO2: 0.01-2.0% (for example, 0.01%, 0.05%, 0.1%, 0.5%, 0.8%, 1.0%, 1.2%, 1.5%, 1.8% or 2.0%), F 2 : 0.5-5.0% (for example, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5 or 5%); wherein the alkaline earth metal oxide includes CaO and MgO, and in molar percentage, CaO is 0.01-4.0% (for example, 0.01%, 0.1%, 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5% or 4.0%), and MgO is 0.5-8.0% (for example, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7% or 8%).
[0024] In the embodiment of the present invention, SiO2 and B2O3 are used as the main components of the glass. SiO2 can serve as a network former of the glass structure. On the one hand, part of B2O3 can form a [BO4] tetrahedral structure and enter the glass silicon oxygen network structure, thereby playing a role of network reinforcement. On the other hand, B2O3 can effectively inhibit ion polarization and thus reduce the dielectric constant and dielectric loss of the glass fiber. By adding a specific type of alkaline earth metal oxide and supplemented with a certain amount of Al2O3, ZrO2, TiO2, LiO2 and F 2 , which can further reduce the dielectric constant and dielectric loss of the glass fiber. At the same time, through the coordinated control of each component, it is beneficial to enhance the process performance of the glass and ensure the stability of glass fiber drawing.
[0025] In the embodiment of the present invention, SiO2 can form a network-formed body of glass structure with silicon-oxygen tetrahedron, and the network-formed body has strong mechanical strength, and the formed network structure has high bond strength, is not easy to polarize under the action of external electric field, and has small losses such as conductivity and relaxation under high frequency, so increasing the content of SiO2 can reduce the dielectric constant and dielectric loss of glass fiber. If the content of SiO2 is too high, it will lead to too high viscosity of glass, and it will be difficult to melt glass and form fiber.
[0026] A certain content of B2O3 can reduce the liquidus temperature of glass and help to increase the temperature range of glass fiber forming. When there is enough free oxygen, part of B2O3 forms a [BO4] tetrahedral structure and enters the glass silicon oxygen network structure, thereby playing a role in network reinforcement. At the same time, on the one hand, the BO bond energy is larger than the Si-O bond energy, which can effectively inhibit ion polarization in the glass structure and thus reduce the dielectric constant and dielectric loss of glass fiber; on the other hand, the presence of B2O3 makes more B 3+ It exists in the form of [BO3] triangles, forming a layered structure. This structure has weak coupling, which can reduce the high-temperature viscosity of the glass and is beneficial to the melting and clarification of the glass.
[0027] When there are enough ions in the glass, Al in Al2O3 3+ It can enter the glass network structure as [AlO4] tetrahedron, which can enhance the densification of the glass network structure, reduce the phase separation tendency of the glass, inhibit the formation of crystal nuclei to improve the forming process performance of the fiber, and improve the mechanical properties, dielectric properties and chemical corrosion resistance of the glass fiber. However, excessive Al2O3 introduction will not only lead to the appearance of a large number of network exosomes, resulting in excessively high melting temperature of the glass and enhanced crystallization tendency, but also lead to problems such as increased dielectric constant and dielectric loss of the glass fiber.
[0028] The addition of alkaline earth metal oxides is beneficial to improving the dielectric constant and ion polarizability of the glass fiber, thereby improving the dielectric constant. However, it is found in the embodiments of the present invention that when at least two alkaline earth metal oxides are present, the dielectric constant and dielectric loss of the glass fiber can be slowed down and show a downward trend. Therefore, in the embodiments of the present invention, appropriate amounts of CaO and MgO are added to further reduce the dielectric loss and dielectric constant of the glass fiber.
[0029] ZrO2 and TiO2 belong to network exosomes in the glass structure. ZrO2 can increase the high-temperature viscosity of glass, improve the glass density and elastic modulus. The polarizability of ZrO2 is lower than that of Al2O3. Adding ZrO2 to glass helps to further reduce the dielectric constant and loss of glass fiber. At the same time, a certain content of TiO2 can increase the density and modulus of glass fiber, and the increase in the dielectric constant of glass fiber is relatively slow compared to alkaline earth oxides. However, excessive content of TiO2 and ZrO2 will not only increase the cost, but also make the viscosity of glass too high, thereby reducing the process performance of glass.
[0030] Li2O can reduce the melting temperature of glass and the forming temperature of fiber, and improve the thermal stability of glass. At the same time, Li2O can be used as a flux to reduce the melting temperature of glass, improve production efficiency, and help form the required glass structure. Furthermore, the addition of appropriate content of Li2O can further reduce the dielectric constant of glass and improve the dielectric properties of glass.
[0031] According to some preferred embodiments, the sum of the molar percentages of SiO2 and B2O3 is 78-85% (for example, it may be 78%, 79%, 80%, 81%, 82%, 83%, 84% or 85%).
[0032] It is found through experimental verification that the dielectric constant of glass fiber is mainly affected by the total polarizability of ions and the number of ions per unit volume. Usually, the dielectric constant increases with the increase of the total polarizability of positive and negative ions in the glass, and decreases with the increase of molar volume. While SiO2 and B2O3 have lower polarizability and higher molar volume, increasing SiO2 and B2O3 helps to reduce the dielectric constant of glass, but the elastic modulus of glass increases with the increase of ionic field strength and the increase of molar volume, showing an opposite trend to the dielectric constant. Therefore, in the embodiment of the present invention, the molar percentage sum of SiO2 and B2O3 is controlled within a reasonable range, so as to be conducive to forming a glass fiber with good mechanical strength based on borosilicate components, and on the basis of ensuring the good process performance of glass fiber, further making the glass fiber have lower dielectric properties.
[0033] According to some preferred embodiments, the alkaline earth metal oxide also includes BaO and SrO; wherein, in molar percentage, BaO is 0.01-2.0% (for example, it can be 0.01%, 0.05%, 0.08%, 0.1%, 0.5%, 0.8%, 1.0%, 1.2%, 1.5%, 1.8% or 2.0%), and SrO is 0.01-2.0% (for example, it can be 0.01%, 0.05%, 0.08%, 0.1%, 0.5%, 0.8%, 1.0%, 1.2%, 1.5%, 1.8% or 2.0%).
[0034] In the present invention, the inventors found that increasing Mg 2+ , Ca 2+ , Ba 2+ , Sr 2+ The content of alkaline earth metal oxides such as CaO and MgO will increase the dielectric constant, ion polarizability and dielectric constant of the glass fiber. However, when multiple alkaline earth ions are present, due to the existence of a blocking effect similar to the mixed alkali effect, the vibration or relaxation of the ions will be hindered, and the increase in dielectric loss will slow down and show a downward trend. Therefore, in the embodiment of the present invention, BaO and SrO are further added on the basis of CaO and MgO to form multiple alkaline earth metal oxides, which is not only conducive to further reducing the dielectric constant of the glass fiber, but also can improve the elastic modulus of the glass fiber.
[0035] According to some preferred embodiments, the ratio of B2O3 to the alkaline earth metal oxide is 2.5 to 7 (for example, 2.5, 3, 4, 5, 6 or 7) in mole percentage.
[0036] In the embodiment of the present invention, B2O3 is a typical network former in the glass. As the content of B2O3 increases, the glass network structure units and arrangement change, resulting in changes in the dielectric properties of the glass. 3+ The polarizability of ions in glass is minimal, so with the addition of B2O3, the dielectric constant of the sample gradually decreases. As the content of alkaline earth metal oxides increases, the density, elastic modulus and dielectric constant of glass fiber will gradually increase. In addition, the dielectric constant and dielectric loss of mixed alkali metal glass are lower than those of single alkali metal glass. Therefore, by adjusting the ratio of boron oxide to other alkaline earth metal oxides, the dielectric properties of glass fiber can be optimized to meet the requirements of low dielectric constant.
[0037] According to some preferred embodiments, the low dielectric glass fiber composition further comprises: ZnO, Y2O3 and P2O5; wherein, in terms of molar percentage, ZnO is 0.01 to 5.0% (for example, 0.01%, 0.05%, 0.1%, 0.5%, 1.0%, 1.5%, 2%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5% or 5.0%), Y2 O3 is 0.01-0.6% (for example, it can be 0.01%, 0.05%, 0.08%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5% or 0.6%), and P2O5 is 0.01-2.0% (for example, it can be 0.01%, 0.05%, 0.1%, 0.5%, 0.8%, 1.0%, 1.2%, 1.5%, 1.8% or 2.0%).
[0038] In the embodiment of the present invention, the low dielectric glass fiber composition further includes a certain amount of ZnO, Y2O3 and P2O5. The three components can further reduce the dielectric constant and dielectric loss of the glass fiber from different aspects. 2+ The mass is greater than that of Mg2+ and Ca 2+ However, since its outer layer has 18 electrons, its electron binding energy is high and the electron displacement polarization is small, it is beneficial to further reduce the dielectric constant and dielectric loss of glass fiber. In addition, it is found in the embodiment of the present invention that when Mg 2+ , Ca 2+ and Zn 2 + When Y2O3 is introduced into glass, they will produce a synergistic effect to further reduce the dielectric constant and dielectric loss of glass fiber. Furthermore, the addition of Y2O3 can aggregate the non-bridging oxygen in the Si-O bond, making the network structure more compact. At the same time, the appropriate content of Y2O3 can also help reduce the dielectric constant and dielectric loss of glass fiber. Excessive introduction not only increases the cost, but also reduces the effect of optimizing the dielectric properties of glass.
[0039] In order to avoid the adverse effects of alkaline earth metal oxides and high-valent oxides on the dielectric properties of glass fibers, F is added to the glass component in the embodiment of the present invention. 2 (in the form of fluoride) and P2O5. - Ions can combine with cations to reduce the ionic radius and polarizability, which is beneficial to further reduce the dielectric constant and dielectric loss of glass fiber. + or Mg 2+ Isocations and F - After combining, the polarizability is lower than that of these ions and O 2-The combined polarizability, lower polarizability is conducive to further ensuring the lower dielectric constant and loss of glass fiber, and fluoride can effectively reduce the high temperature viscosity of glass melt, thereby reducing the drawing temperature and improving the drawing process performance. At the same time, the introduction of an appropriate content of P2O5 into silicate glass helps to reduce the number of non-bridging oxygen in silicate glass, aggregate the network structure, and help reduce the dielectric constant of glass.
[0040] According to some preferred embodiments, the sum of the molar percentages of ZrO2 and Y2O3 is 0.2-2% (e.g., 0.2%, 0.5%, 0.8%, 1.0%, 1.5% or 2.0%);
[0041] According to some preferred embodiments, F 2 The sum of the molar percentages of P2O5 and P2O5 is 0.6-7% (for example, it can be 0.6%, 1.0%, 2.0%, 3%, 4.0%, 5.0%, 6.0% or 7.0%).
[0042] In the embodiment of the present invention, since ZrO2 and Y2O3 are both network exosomes in the glass structure, after being added to the glass components, the elastic modulus of the glass structure can be enhanced in different ways, and the dielectric constant and dielectric loss of the glass fiber can be reduced. By controlling the total content of the two in molar percentage, it is beneficial to better regulate the elastic modulus and dielectric properties of the glass fiber while ensuring good process performance of the glass fiber. However, if the content of the two is too high, not only will the high-temperature viscosity of the glass increase and the process performance of the glass be reduced, but the effect on optimizing the dielectric properties of the glass will also be reduced.
[0043] According to some preferred embodiments, the low dielectric glass fiber composition comprises the following components, in mole percentage: SiO2: 55.5-58% (for example, 55.5%, 56%, 56.5%, 57%, 57.5% or 58%), B2O3: 21.5-31.5% (for example, 21.5%, 22%, 22.5%, 23%, 23.5%, 24%, 24.5%, 25.5%, 26.5%, 27.5%, 28.5%, 29.5%, 30.5%, 31.5%, 32.5%, 33.5%, 34.5%, 35.5%, 36.5%, 37.5%, 38.5%, 39.5%, 40.5%, 41.5%, 42.5%, 43.5%, 44.5%, 45.5%, 46.5%, 47.5%, 48.5%, 49.5%, 50.5%, 51.5%, 52.5%, 53.5%, 54.5%, 55.5%, 56.5%, 57.5%, 58.5%, 59.5%, 60.5%, 61.5%, 62.5%, 63.5%, 64.5%, 65.5%, 66.5%, 67.5%, 68.5%, 69.5%, 70.5%, 71.5%, 72.5%, 73.5%, 74.5%, 75.5%, 76.5%, 77.5%, 78.5%, 79.5%, 80.5%, 81. 25%, 25.5%, 26%, 27.5%, 28%, 28.5%, 29%, 30%, 30.5%, 31% or 31.5%), Al2O3: 1.0-5.0% (for example, 1.0%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5.0%), alkaline earth metal oxide: 3-10% (for example, 3%, 3.5%, 4%, 4 .5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5% or 10%), ZrO2: 0.01-1.0% (for example, 0.01%, 0.02%, 0.05%, 0.08%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1.0%), TiO 2: 0.5-3.5% (for example, 0.5%, 0.8%, 1.0%, 1.2%, 1.5%, 1.8%, 2.0%, 2.2%, 2.5%, 2.8%, 3.0%, 3.2% or 3.5%), LiO2: 0.01-2.0% (for example, 0.01%, 0.05%, 0.08%, 1.0%, 1.2%, 1.5%, 1.8% or 2.0%), F 2 :0.5~5.0% (for example, 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5% or 5.0%), ZnO:0.05~4.0% (for example, 0.05%, 0.1%, 0.5%, 1.0%, 2.0%, 3.0% or 4.0%), Y2O3:0.05 ~0.5% (for example, it can be 0.05%, 0.08%, 0.1%, 0.2%, 0.3%, 0.4% or 0.5%), P2O5: 0.05~2.0% (for example, it can be 0.05%, 0.08%, 0.1%, 0.3%, 0.5%, 0.7%, 0.9%, 1.0%, 1.2%, 1.5%, 1.8% or 2.0%);
[0044] The alkaline earth metal oxides include CaO, MgO, BaO and SrO. In terms of molar percentage, CaO is 0.3-4.0% (for example, 0.3%, 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5% or 4.0%), and MgO is 0.9-7.5% (for example, 0.9%, 1.0%, 2.0%, 3.0%, 4.0%, 5.0%, 6.0%, 7.5%). .0% or 7.5%), BaO is 0.02-1.5% (for example, it can be 0.02%, 0.05%, 0.08%, 0.1%, 0.2%, 0.5%, 0.8%, 1.0%, 1.2% or 1.5%), and SrO is 0.02-1.5% (for example, it can be 0.02%, 0.05%, 0.08%, 0.1%, 0.2%, 0.5%, 0.8%, 1.0%, 1.2% or 1.5%).
[0045] In the embodiments of the present invention, through a large number of experimental screenings and data summarization, it is found that when a specific type of oxide is used and its proportion and addition amount are controlled, a suitable positive accumulation effect can be achieved, which is beneficial to further reduce the dielectric constant and dielectric loss of the glass fiber while ensuring a good elastic modulus of the glass fiber, and the drawing process of the glass fiber is more stable and has excellent process performance.
[0046] It should be noted that the unavoidable impurities in the present invention are Na2O, K2O and Fe2O3 introduced from the raw materials, and the total content of such substances should be controlled within 0.3%.
[0047] The present invention also provides a method for preparing low dielectric glass fiber from the low dielectric glass fiber composition described in any one of the above, the method comprising the following steps:
[0048] (1) stirring and mixing each component according to mole percentage to obtain a low dielectric glass fiber composition;
[0049] (2) melting the low dielectric glass fiber composition to obtain homogeneous glass;
[0050] (3) Drawing the homogeneous glass to obtain the low dielectric glass fiber.
[0051] In an embodiment of the present invention, the content of each component raw material is optimized and regulated to obtain the constituent raw materials of the low dielectric glass fiber. During the preparation process, the raw materials can be melted into a glassy state and then quenched with water, and then added to a platinum crucible for drawing, thereby preparing the low dielectric glass fiber.
[0052] The low-dielectric glass fiber in the embodiment of the present invention has relatively low dielectric properties. At 10 GHz, the dielectric loss of the glass fiber is 0.001-0.0018, and the dielectric constant is 3.9-4.1.
[0053] It should be noted that, in the embodiments of the present invention, when melting, full oxygen combustion, full electric melting or a combination of fire and electricity can be used for kiln melting to form homogeneous glass. Further, the kiln for melting glass can be a melting furnace composed of refractory materials that are resistant to high temperatures and erosion by glass liquid, such as electric fused high zirconium bricks, dense zirconium bricks, electric fused mullite bricks, etc. At the same time, a platinum-substituting furnace constructed of refractory dense zirconium bricks, corundum bricks, electric fused chromium zirconium corundum bricks, and mullite can be used for wire drawing production, that is, first using the low-dielectric glass fiber composition of the present invention to melt glass, and then using glass to draw glass fibers, or using the kiln passage constructed of the above-mentioned refractory materials for one-step wire drawing production.
[0054] The melting temperature and fiber forming temperature of the low dielectric glass fiber composition components in the embodiments of the present invention are relatively high, and a melting furnace and a platinum-substituting furnace or a one-step tank furnace constructed of refractory materials that are resistant to high temperatures and erosion by molten glass are required for glass melting and fiber preparation.
[0055] An embodiment of the present invention further provides an application of any of the above-mentioned low-dielectric glass fiber high-frequency circuit boards.
[0056] The low dielectric glass fiber prepared in the embodiment of the present invention can be used in the electronics industry to manufacture copper-clad laminates, printed circuit boards, etc. Due to the characteristics of low dielectric constant and low dielectric loss, it helps to improve the signal transmission speed and efficiency in high-speed data transmission and high-frequency circuit boards. In the field of aerospace, low dielectric glass fiber can be used to manufacture lightweight and high-strength structural parts. Low dielectric glass fiber is an indispensable engineering material in the fields of high-order communications, aerospace, etc.
[0057] In order to more clearly illustrate the technical solution and advantages of the present invention, a low-dielectric glass fiber composition, a low-dielectric glass fiber and a preparation method thereof are described in detail below through several embodiments.
[0058] According to the raw material composition of each formula listed in Table 1, the required mass percentage of various raw materials in Examples 1 to 13 and Comparative Examples 1 to 2 is calculated respectively, accurately weighed and evenly mixed to form the composition raw materials, pneumatically mixed and transported to the kiln charging port, and fed by an automatic feeder, and melted at about 1600°C in a full electric melting or thermal power combined kiln to obtain a clarified and homogenized glass liquid. The molten glass liquid is prepared into glass balls, and the molten glass balls are melted again at 1550°C, and a 400 or more bushing is used to control the glass fiber forming process parameters (liquid level, hot spot temperature, bushing temperature, drawing machine speed, etc.), and drawn into a continuous glass fiber with a diameter of 8 to 22 μm, and the fiber is tested for performance, and the results are shown in Table 1.
[0059] Table 1
[0060]
[0061]
[0062]
[0063] The glass density is tested using GB / T 5432 "Glass Density Determination Buoyancy Method". The liquidus temperature is determined using a gradient crystallization temperature test furnace, with reference to the standard ASTM C829. After the sample is placed in a platinum boat, it is placed in a gradient temperature furnace heated to 1400°C, kept warm for 2 hours, taken out to observe the crystallization position, and the upper limit of the crystallization temperature is calculated based on the temperature gradient. The high-temperature viscosity is determined using the American BROOKFIELD high-temperature viscometer, with reference to the standard (ASTM C965). Specifically, the sample is placed in a platinum crucible, placed in a furnace heated to 1500°C, and then the rotor is immersed in the high-temperature glass liquid, kept warm for 1 hour, and the high-temperature viscosity of the glass liquid is tested by the torque of the rotor.
[0064] It can be seen from Table 1 that the low dielectric glass fibers prepared by using the optimized raw material components and content combinations in Examples 1 to 9 not only have good process performance, but also have excellent dielectric properties, specifically manifested in lower dielectric constants and dielectric losses.
[0065] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A low dielectric glass fiber composition, characterized in that: The low dielectric glass fiber composition comprises the following components in molar percentage: SiO2: 54-60%, B2O3: 21-32%, Al2O3: 1.0-9.5%, alkaline earth metal oxides: 3-16%, ZrO2: 0.01-4.0%, TiO2: 0.1-4.0%, LiO2: 0.01-2.0%, F2: 0.5-5.0%; wherein the alkaline earth metal oxides comprise CaO and MgO, and in molar percentage, CaO is 0.01-4.0%, and MgO is 0.5-8.0%.
2. The low dielectric glass fiber composition according to claim 1, characterized in that: The sum of the molar percentages of SiO2 and B2O3 is 78 to 85%.
3. The low dielectric glass fiber composition according to claim 1, characterized in that: The alkaline earth metal oxide also includes BaO and SrO; wherein, in terms of molar percentage, BaO is 0.01-2.0%, and SrO is 0.01-2.0%.
4. The low dielectric glass fiber composition according to claim 1, characterized in that: In terms of molar percentage, the ratio of B2O3 to the alkaline earth metal oxide is 2.5 to 7.
5. The low dielectric glass fiber composition according to claim 3, characterized in that: The low dielectric glass fiber composition also includes: ZnO, Y2O3 and P2O5; wherein, in terms of molar percentage, ZnO is 0.01-5.0%, Y2O3 is 0.01-0.6%, and P2O5 is 0.01-2.0%.
6. The low dielectric glass fiber composition according to claim 5, characterized in that: The sum of the molar percentages of ZrO2 and Y2O3 is 0.2-2%.
7. The low dielectric glass fiber composition according to claim 5, characterized in that: F 2 The sum of the molar percentages of P2O5 and P2O5 is 0.6-7%.
8. The low dielectric glass fiber composition according to claim 1, characterized in that: The low dielectric glass fiber composition comprises the following components in molar percentage: SiO2: 55.5-58%, B2O3: 21.5-31.5%, Al2O3: 1.0-5.0%, alkaline earth metal oxide: 3-10%, ZrO2: 0.01-1.0%, TiO2: 0.5-3.5%, LiO2: 0.01-2.0%, F 2 : 0.5-5.0%, ZnO: 0.05-4.0%, Y2O3: 0.05-0.5%, P2O5: 0.05-2.0%; wherein the alkaline earth metal oxides include CaO, MgO, BaO and SrO, in molar percentage, CaO is 0.3-4.0%, MgO is 0.9-7.5%, BaO is 0.02-1.5%, SrO is 0.02-1.5%.
9. A method for preparing low dielectric glass fiber from the low dielectric glass fiber composition according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: (1) stirring and mixing each component according to mole percentage to obtain a low dielectric glass fiber composition; (2) melting the low dielectric glass fiber composition to obtain homogeneous glass; (3) Drawing the homogeneous glass to obtain the low dielectric glass fiber.
10. Use of the low dielectric glass fiber according to claim 9 in high frequency circuit boards.
Citation Information
Cited By
Low dielectric glass fiber composition, glass fiber and preparation method thereof
CN121225884A
Low dielectric glass fiber compositions, glass fibers, and methods of making the same
CN121225884B
Electronic-grade glass fiber composition, glass fiber cloth and preparation method thereof
CN121248146A
A low dielectric constant high flexibility glass fiber and a method for preparing the same
CN122647106A
A low dielectric constant high flexibility glass fiber and a method for preparing the same
CN122647106B